Results of first stage brachiobasilic and brachiobrachial fistula creation: Implications for staged versus single procedure decision making. Issue 5 (September 2022) - Ottinger, Mary; Picone, Desiree; Hseih, Katrina; Wooster, Mathew; London, Mark J; Ross, John R; Illig, Karl A
Introduction: Transposed brachiobasilic AV fistulas (BVT) have increasingly been performed in two stages. Published reports give conflicting results, perhaps in part as many reports of staged procedures eliminate those patients who "fail" the first stage (i.e. are lost to follow-up in addition to anatomic failure). Methods: A prospectively maintained database was reviewed to identify all patients at two institutions who underwent the first stage of planned two-stage BVT by the senior author. Success in this context was defined as patients who eventually underwent second stage fistula creation, leaving the operating room after the second stage with a patent, transposed fistula. Results: From October 2012 to June 2020, 218 patients underwent first-stage procedures. At the first visit, 185 (85%) of fistulas were patent, 23 (11%) were occluded, 8 (4%) of patients were lost to follow-up, and 2 (1%) died. In the interval before the second operation, another eight (4%) patients were lost to follow-up, two were cancelled for medical reasons, and two declined surgery, leaving a total of 173 patients who made it to the second stage (80%). At operation, four patients were found to have unusable veins, leaving a total of 169 patients who completed both stages. If all patients who underwent first stage are included, 77% of patients entering this pathway left the OR after their second stage with patent access. If those lost to follow-up are excluded, this number increases to 84%, while if all those lost to follow-up are assumed to mature, success increases to 85%. Conclusions: Depending on results in patients lost to follow-up, between 77% and 85% of patients undergoing first stage brachiobasilic fistulae undergo successful second stage transposition. These numbers are equivalent or slightly lower than published maturation rates for single-stage BVT, so there is little margin for failure at the second stage.